(untitled) (Revista Cocar, 2025)
Abstract Does the school have a future? Children aged 5 and 6 from a public school in Rio Grande do Norte answer this question. Their narratives, produced using the methodological strategies of Machines and Time Capsules, are considered legitimate for a cultural analysis based on the fields of Cultural Studies in Education and Research with Children. The analysis revealed two central categories: "What schools are for," examining the functions attributed to schools, and "The future of the school," with narratives about a school full of technological, cultural, and aesthetically beautiful artifacts and, to a lesser extent, narratives about a future without schools, in which learning would take place at home or not at all. In general, children legitimize school as essential for the transmission of knowledge and socialization. Keywords: School in the Future; Children and Narratives; Cultural Studies and Education. Resumo A escola tem futuro? Crianças de 5 e 6 anos da Educação Infantil de uma escola pública do Rio Grande do Norte respondem essa questão. Suas narrativas — produzidas por meio das estratégias metodológicas Máquina e Cápsula do Tempo — são consideradas legítimas para a realização de uma análise cultural a partir dos campos dos Estudos Culturais em Educação e das Pesquisas com Crianças. A análise revelou duas categorias centrais: “Para que servem as escolas”, examinando as funções atribuídas à escola, e “O futuro da escola”, com narrativas sobre uma escola repleta de artefatos tecnológicos, culturais e esteticamente bonitos e, em menor número, narrativas sobre um futuro sem escolas, no qual a aprendizagem ocorreria em casa ou não aconteceria. Em geral, as crianças legitimam a escola como essencial para a transmissão de saberes e a formação social. Palavras-chave: Escola no Futuro; Crianças e Narrativas; Estudos Culturais e Educação.